The Student-Centered Learning Approach In Islamic Religious Education As A Strategy For Preventing Radicalism: A Systematic Literature Review - Wahdini, Wahdini; Haris, Abdul (UNIVERSITAS PAKUAN, 2025)
The rise of radicalism among students poses a serious challenge to the national education system, particularly in the teaching of Islamic Religious Education (PAI). This situation indicates an imbalance between the ideal of Islamic education, which is oriented towards moderation, and pedagogical practices that are still teacher-centered and tend to be doctrinal. One pedagogical approach that is considered capable of overcoming this problem is Student-Centered Learning (SCL), a learning model that prioritizes the active involvement of students in constructing knowledge, developing critical reflection, and internalizing contextual and humanistic religious values. This study aims to systematically examine the relevance and effectiveness of applying SCL in PAI as a strategy to prevent radicalism in educational institutions. This study uses the Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines, analyzing 30 scientific articles published between 2015 and 2025 from the Scopus, ERIC, SpringerLink, Taylor Francis, and DOAJ databases. The results show that the application of SCL encourages a paradigm shift in learning from a teacher-centered approach to a participatory, reflective, and collaborative model. SCL has been proven to contribute to strengthening critical thinking skills, social empathy, and religious moderation values such as tolerance, justice, and balance. Therefore, SCL functions not only as an effective pedagogical strategy but also as an ideological instrument for building inclusive religious awareness and rejecting extremism. This study recommends curriculum reform, improvement of teacher competence, and SCL-based Islamic education policies to strengthen religious moderation and promote sustainable social peace